Gotowość do zmiany na przykładzie badań przedstawicieli kadry kierowniczej - Lubrańska, Anna (Acta Universitatis Lodziensis. Folia Psychologica, 2011)
The character of work process, having evolved in the recent years, imposes new requirements on the participants of contemporary organizations. The aim of this article is to verify which of variables are important for readiness to change of managers. Therefore the statistical analyses of the empirical material were conducted towards recognition of the strongest determinants of readiness to change of managers. The results of the statistical analyses prove that the variables of greatest importance to readiness to change are of subjective character.